Sustainable Stabilization of Clay Soil with Rice Husk Ash - Abdulrahman, Shaimaa M.; Al Kindi, Ghayda Yaseen; Ihsan, Elaf Abd Al–AzaI (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Groundwater-exposed liquid clay soil (CL) makes foundations unstable. This study used recycled rice husk ash and treated clay soil exposed to groundwater with low-cost, environmentally friendly materials. This paper presents a recent prediction of three equations that link the plastic index to soil strength, cohesion, and the bearing capacity of a foundation. This prediction takes into account the soil’ characteristics before and after treatment, as well as the cumulative load until failure. It creates four models before and after treatment, as well as a different time period after treatment, to study the situation. This is achieved by mixing the best-added ratios in depth equal to the foundation width. The limitations of Atterberg, and the unconfined compressive strength were tested using three additives: cement alone, rice husk ash alone, and rice husk ash plus 2% cement. The percentages were 4%, 6%, 8%, and 10% of the soil weight. It was noted that soil activity dropped from 0.98 to 0.31, 0.32, and 0.42 for cement 8%, rice husk ash 8% plus 2% cement, and 8% RHA alone. The foundation bearing capacity increased from 49 at 1 day to 115, 275, and 460 Kpa for 7, 14, and 28 days, respectively.